Diversity of some organisms in Chiang Mai Rajabhat University, Mae Rim Campus, Chiang Mai Province - Supahan, Nattida; Kunpradid, Tatporn; Joradol, Atinut; Leelahakriengkrai, Pongpan (Progress in Applied Science and Technology, 2017)
The objective of this research is to study the diversity of phytoplankton, benthos, plants, birds, as well as water and soil quality in the area of Mae Rim Campus of Chiang Mai Rajabhat University, Mae Rim district in Chiang Mai province in Thailand. This research was conducted from October 2013 to September 2014. The study found that there were 5 divisions of phytoplankton consisting of 31 species from 22 genera with Ankistrodesmus falcatus, Staurastrum smithii, Cosmarium contractum and Staurastrum sp. as being most prominent. Two phyla consisting of 12 families from 8 Orders of benthos were found and the most abundance species were Macrobrachium sp. (freshwater prawns) and Rhagadotarsus sp. (water striders). Furthermore12 families consisting of 15 species of plants were found, and the most abundance species were Dipterocarpus tuberculatus and Shorea siamensis. Moreover, 15 orders consisting of 106 species from 77 genera within 43 families of birds were also found. That includes 83 resident species, 22 were winter visitors species and one passage migrant species. The concentration of nutrient in the soil was classified as low. The analysis showed that the amount of phosphorus and potassium in soil were 4.50-5.07 mg/kg and 35.67-95.67 mg/kg, respectively. However, from a biodiversity perspective, it can be concluded that the terrestrial and aquatic ecosystem in Mae Rim Campus, Chiang Mai Rajabhat University is suitable for using as local learning areas for students and communities. In addition, the university can use the database of this study to make decisions and to develop a policy on campus development in the future.